Mini but mighty: microRNAs in the pathobiology of periodontal disease. (October 2015) - Kebschull, Moritz; Papapanou, Panos N.
Abstract: MicroRNAs (miRNAs) are a family of small, noncoding RNA molecules that negatively regulate protein expression either by inhibiting initiation of the translation of mRNA or by inducing the degradation of mRNA molecules. Accumulating evidence suggests that miRNA‐mediated repression of protein expression is of paramount importance in a broad range of physiologic and pathologic conditions. In particular, miRNA‐induced dysregulation of molecular processes involved in inflammatory pathways has been shown to contribute to the development of chronic inflammatory diseases. In this review, first of all we provide an overview of miRNA biogenesis, the main mechanisms of action and the miRNA profiling tools currently available. Then, we summarize the available evidence supporting a specific role for miRNAs in the pathobiology of periodontitis. Based on a review of available data on the differential expression of miRNAs in gingival tissues in states of periodontal health and disease, we address specific roles for miRNAs in molecular and cellular pathways causally linked to periodontitis. Our review points to several lines of evidence suggesting the involvement of miRNAs in periodontal tissue homeostasis and pathology. Although the intricate regulatory networks affected by miRNA function are still incompletely mapped, further utilization of systems biology tools is expected to enhance our understanding of the pathobiology of periodontitis.